2012
DOI: 10.5219/231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lifetime exposure of sublethal doses of cadmium to selected parameters of carbohydrate metabolism

Abstract: The aim of the study was to assess the effects of exposure to low doses of cadmium dissolved in drinking water (at a concentration 200 times higher than the maximum permissible dose) on selected parameters of carbohydrate metabolism in 20 Wistar rats. Animals were divided into two groups – control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Micronutrient elements such as Fe, Cu, Zn, Se and macronutrients Ca, Mg, are essential for many biological functions (Kazi et al, 2009;Lukačínová et al, 2012). Deficiencies of such elements contribute significantly to the global burden of disease; however, if present at higher levels, they can have a negative effect on human health.…”
Section: Volume 12 455mentioning
confidence: 99%
“…Micronutrient elements such as Fe, Cu, Zn, Se and macronutrients Ca, Mg, are essential for many biological functions (Kazi et al, 2009;Lukačínová et al, 2012). Deficiencies of such elements contribute significantly to the global burden of disease; however, if present at higher levels, they can have a negative effect on human health.…”
Section: Volume 12 455mentioning
confidence: 99%
“…Ibrahim and cols in 2012 [125] had reported hyperglycemic effect on rats exposed to different doses of lead acetate, just as Adham et al did in birds in 2011 [126], however other authors have found in rats hypoglycemia, after low doses of lead dissolved in water [127]. It is necessary to understand the mechanism and the reason for this dual effect.…”
Section: Metals and Glucose Metabolismmentioning
confidence: 98%
“…Micronutrient elements such as Fe, Cu, Zn, Se and macronutrients Ca, Mg, are essential for many biological functions [14,15]. Deficiencies of such elements contribute significantly to the global burden of disease; however, if present at higher levels, they can have a negative effect on human health.…”
Section: Introductionmentioning
confidence: 99%